Hydroxy-Substituted Azacalix[4]Pyridines: Synthesis, Structure, and Construction of Functional Architectures - Zhang, En-Xuan; Wang, De-Xian; Wang, Mei-Xiang (Frontiers in Chemistry, 2019)
A number of hydroxyl-substituted azacalix[4]pyridines were synthesized using Pd-catalyzed macrocyclic “2+2” and “3+1” coupling methods and the protection-deprotection strategy of hydroxyl group. While the conformation of the these hydroxyl-substituted azacalix[4]pyridines are fluxional in solution, in the solid state they adopted shape-persistent 1,3-alternate conformations. Besides, X-ray analysis revealed that the existence of hydroxy groups on the para-position of pyridine facilitated the formation of solvent-bridged intermolecular hydrogen bonding for mono-hydroxyl substituted while partial tautomerization for four-hydroxyl substituted macrocycles, respectively. Taking the hydroxyl substituted azacalix[4]pyridines as molecular platforms, multi macrocycle-containing architectures and functional building blocks were constructed. The self-assembly behavior of the resulting building blocks was investigated in crystalline state.